Legal Contradictions in Land Acquisition for Community-Based Tourism Villages in Indonesia - Azna Abrory Wardana; Imam Koeswahyono; Iwan Permadi; Ngesti Dwi Prasetyo (E-Journal of Tourism, 2025)
Tourism village development in Indonesia is expanding rapidly, with tourist arrivals projected to reach 13.74 million in 2024. Yet the legal framework for land acquisition has not adapted to this growth. The core issue lies in the tension between the public interest doctrine in Law No. 2 of 2012 on Land Acquisition, which legitimizes compulsory state power, and the mandate of community-based tourism (CBT) under Law No. 6 of 2014 on Villages and Law No. 10 of 2009 on Tourism, which requires participatory, community-driven development. This doctrinal gap produces uncertainty over how land acquisition for tourism villages should proceed in ways that advance development while safeguarding community rights. This study employs a normative legal method, combining statutory interpretation and conceptual analysis of “public interest,” “participation,” and “compensation” in the Land Acquisition Law, alongside relevant provisions of the Village and Tourism Laws and judicial decisions in acquisition disputes. The findings highlight three contradictions: first, Article 10’s expansive definition of “public interest” enables commercial tourism projects to qualify as public uses; second, consultation procedures are reduced to formalities without substantive participation; and third, NJOP-based compensation undervalues land and disregards communal tenure. This article contributes by proposing a reform agenda: redefining public interest with measurable criteria, integrating Free, Prior, and Informed Consent (FPIC), harmonizing sectoral laws, and mandating community consent mechanisms to balance tourism development with the protection of local land rights.